Residual compost from the production of Bactris gasipaes Kunth and Pleurotus ostreatus as soil conditioners for Lactuca sativa ‘Veronica’ - Marcelo Barba Bellettini; Sebastião Bellettini; Francisco Menino Destéfanis Vítola; Fernanda Assumpção Fiorda; Agenor Maccari Junior; Carlos Ricardo Soccol (Semina: Ciências Agrárias, 2017)
This study evaluated the residual compost from the production of Bactris gasipaes Kunth (pupunha heart of palm) (RP) and the mushroom Pleurotus ostreatus (RM). The residuals were used as soil conditioners for Lactuca sativa ‘Veronica’ crops. After adding RP and RM to the soil, all treatments exhibited similar behaviors and soils in each treatment were classified as eutrophic. Soil treatments involving increased application of residual compost resulted in the production of lettuce with greater widths because of an increase in the angle between the stem and leaf, resulting from a lack of nitrogen available to the plant. Soil treatments with 5% of RP and RM resulted in a 1.7 and 1.2 times (44% and 22%, respectively) decrease in dry weight of lettuce, as compared to the soil without residual compost addition. The addition of RP and RM as soil substrate reduced the growth of lettuce compared to the soil without residual compost. In general, the possibility of replacing chemical fertilizers (NPK) with RP or RM without previous composting was found to be inefficient. The resultant dry weight parameters were below the commercial level, and a complete period of composting RP and RM was deemed necessary for incorporating nitrogen into the soil. Lignocellulosic mushrooms such as Pleurotus spp. present highly fibrous residual compost with low nitrogen content, thus requiring a full period of composting before subsequent use in soil enrichment for various crops.